(untitled) (Research, Society and Development, 2022)
In recent years, the term sustainable development has entered the vocabulary of the most distinct areas of society, from universities, business circles and even the complex financial market. Controversies aside, the understanding is unanimous that the development of societies involves the interrelation of various social aspects, which need to equate economic expansion together with social inclusion and environmental preservation, directing their results to deliver a better quality of life. The objective of this study was to evaluate the impacts of cooperativism on local sustainable development in a rural community in the interior of Amazonas. Interviews were carried out in the community with participants of the cooperative and members who did not participate in it. In the light of four dimensions of sustainability, it was possible to identify the influence of cooperativism on the sustainable development of the community, presenting the most significant points and discussing the role of this form of organization in facing the challenges and opportunities of the Amazon region.